(untitled) (Práxis Educativa, 2023)
Entrevistadoras: Angela Scalabrin Coutinho Sandra Fernandes Leite Entrevistados: Tomáš Foltýnek Rubén Comas Forgas Frederico Garcia Fernandes Sonia Maria Ramos Vasconcelos Jefferson Mainardes